Green fluorescent protein transgene driven by Kit regulatory sequences is expressed in hematopoietic stem cells - Francesco Cerisoli; Letizia Cassinelli; Giuseppe Lamorte; Stefania Citterio; Francesca Bertolotti; Maria Cristina Magli; Sergio Ottolenghi (Haematologica, 2009)
Background The transcriptional regulation of stem cell genes is still poorly understood. Kit, encoding the stem cell factor receptor, is a pivotal molecule for multiple types of stem/progenitor cells. We previously generated mouse lines expressing transgenic green fluorescent protein under the control of Kit promoter/first intron regulatory elements, and we demonstrated expression in hematopoietic progenitors.Design and Methods In the present work we investigated whether the transgene is also expressed in hematopoietic stem cells of adult bone marrow and fetal liver. To this purpose, we tested, in long-term repopulating assays, cell fractions expressing different levels of green fluorescent protein within Kit-positive or SLAM-selected populations.Results The experiments demonstrated transgene expression in both fetal and adult hematopoietic stem cells and indicated that the transgene is transcribed at distinctly lower levels in hematopoietic stem cells than in pluripotent and committed progenitors.Conclusions These results, together with previous data, show that a limited subset of DNA sequences drives gene expression in number of stem cell types (hematopoietic stem cells, primordial germ cells, cardiac stem cells). Additionally, our results might help to further improve high level purification of hematopoietic stem cells for experimental purposes. Finally, as the Kit/green fluorescent protein transgene is expressed in multiple stem cell types, our transgenic model provides powerful in vivo system to track these cells during development and tissue regeneration.